Peningkatan Daya Saing UMKM Melalui Optimalisasi Penyusunan Laporan Keuangan - Wa Ode Rayyani; Muhammad Nur Abdi; Endang Winarsi; W Warda (Universitas Muhammadiyah Parepare)
This activity aims to improve the competitiveness of MSMEs by optimizing the preparation of financial statements. The background of the activity is the phenomenon of small business people, such as Micro Enterprises and Small Businesses which are generally engaged in the home industry, not yet realizing the importance of financial reports, even consider not needing financial reports because it is quite troublesome. Most transactions are recorded in memory, only a few are left in the notes that are "ala levels" as well. Because of the chaotic financial records, micro and small businesses have weak competitiveness due to not knowing their business position, whether they are profitable or even losing money. The results of the process are processed based on the type of qualitative data with data collection methods carried out using observation, in-depth interviews, and documentation. The results of the implementation of the activities indicate that most of the Micro and Small Business actors have not carried out accounting records properly and correctly. Various reasons for not recording include, among others, because accounting records are very inconvenient or even there is no evidence of transactions made. As a partner in this assistance is a micro-scale household business engaged in the "Makassar specialty" snacks managed by Ms. Rosmala and has been running for three years. The results of the mentoring show the interest of partners in financial reporting after the training.